2008
DOI: 10.4049/jimmunol.181.9.6178
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1+c-kit+ Bone Marrow Cells Give Rise to CD103+ and CD103− Dendritic Cells with Distinct Functional Properties

Abstract: Dendritic cells (DC) represent a rather heterogeneous cell population with regard to morphology, phenotype, and function and, like most cells of the immune system, are subjected to a continuous renewal process. CD103+ (integrin αE) DC have been identified as a major mucosal DC subset involved in the induction of tissue-specific homing molecules on T cells, but little is known about progenitors able to replenish this DC subset. Herein we report that lineage (lin)−CX3CR1+c-kit+ (GFP+c-kit+) bone marrow cells can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 40 publications
(37 reference statements)
1
54
0
Order By: Relevance
“…CD103 1 DCs take up antigens less efficiently than CD103 -DCs. 38 Consistently, .50% of GM-DCs incorporate high levels of ovalbumin (OVA), compared with ,10% of FL-DCs and iCD103-DCs ( Figure 5A). …”
Section: Icd103-dcs Cross-present Cell-associated Antigensmentioning
confidence: 54%
“…CD103 1 DCs take up antigens less efficiently than CD103 -DCs. 38 Consistently, .50% of GM-DCs incorporate high levels of ovalbumin (OVA), compared with ,10% of FL-DCs and iCD103-DCs ( Figure 5A). …”
Section: Icd103-dcs Cross-present Cell-associated Antigensmentioning
confidence: 54%
“…Recently, it has been shown that CD103 1 (integrin a E ) DCs share some of the properties of the CD8 1 DCs, including crosspresentation capability and dependence on the Batf3 (Jun dimerization protein p21SNFT) transcription factor for their development [24,25]. Although it has been described that 50-70% of splenic CD8 1 DCs coexpress CD103 [12,26], we and others [27] found much lower proportions of these cells. In both C57BL/6 and Balb/c mice, only 10-20% of splenic CD8 1 DCs showed weak expression of CD103.…”
mentioning
confidence: 58%
“…6B). However, we cannot rule out the possibility that CD103 [12,26]. Accordingly, it has been recently shown in two independent studies that splenic CD8 1 DCs are heterogeneous regarding their ability to cross-present antigens [11,12].…”
Section: Licensing the Defect Of Splenic Cd8mentioning
confidence: 87%
“…These cells might play a role in the additional activation of LN-primed T cells and/or be important as local antigen-presenting cells that stimulate effector/memory T cells that are directly recruited to inflammatory sites (37,48,49). Furthermore, they could also play a role in the production of cytokines and chemokines that are involved in the attraction of different inflammatory cell types (13). Previous studies of RSV-infected mice reported the increase of cDC and pDC populations in the lung, similar to our observations ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…cDC can be further divided based on the expression of surface markers and anatomic location. cDC in the tissue and cDC in lymph nodes (LN) appear to be different subsets arising from different pools of progenitor cells and with specialized functions (13,17,30,33,46). In the mouse lung, two major cDC populations are derived from blood monocytes.…”
mentioning
confidence: 99%